Trusted Time-Based Verification Model for Automatic Man-in-the-Middle Attack Detection in Cybersecurity - James Jin Kang; Kiran Fahd; Sitalakshmi Venkatraman (Cryptography, 2018)
Due to the prevalence and constantly increasing risk of cyber-attacks, new and evolving security mechanisms are required to protect information and networks and ensure the basic security principles of confidentiality, integrity, and availability—referred to as the CIA triad. While confidentiality and integrity can be achieved using Secure Sockets Layer (SSL)/Transport Layer Security (TLS) certificates, these depend on the correct authentication of servers, which could be compromised due to man-in-the-middle (MITM) attacks. Many existing solutions have practical limitations due to their operational complexity, deployment costs, as well as adversaries. We propose a novel scheme to detect MITM attacks with minimal intervention and workload to the network and systems. Our proposed model applies a novel inferencing scheme for detecting true anomalies in transmission time at a trusted time server (TTS) using time-based verification of sent and received messages. The key contribution of this paper is the ability to automatically detect MITM attacks with trusted verification of the transmission time using a learning-based inferencing algorithm. When used in conjunction with existing systems, such as intrusion detection systems (IDS), which require comprehensive configuration and network resource costs, it can provide a robust solution that addresses these practical limitations while saving costs by providing assurance.